PENDIDIKAN DAN PELATIHAN PENGENDALIAN TERPADU PENYAKIT CVPD (CITRUS VEIN PHLOEM DEGENERATION) PADA PERTANAMAN JERUK DI DESA PELAGA, KECAMATAN PETANG, KABUPATEN BADUNG - ADIARTAYASA, WAYAN; SIMPATI, KETUT; SUMIARTHA, KETUT (Buletin Udayana Mengabdi, 2012)
ABSTRACT Education and training on integrated pest management (IPM) of CVPD (Citrus Vein Phloem Degeneration) was held at Pelaga village, Badung regency on 22 September 2005. The activities aimed to improve knowledge of the farmers about CVPD and factors influencing the intensity, insect vector and integrated pest management of CVPD. The topics convered were disease symptons, and pathogen bacteria, Diaphorina citri are as vector insect infection mechanism, disease distribubution and integrated management of CVPD. The training was attended by 26 participants from local groups of Pelaga village. The method used in activities were lectures, demonstration and practical work in the citrus field. All participants enthusiastically took part and hoped to have the next intensive traning of citrus culture.